Entrepreneurial Leadership and Innovation: Driving Start-Up Success - Andi Setiawan; Dewi Susanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study examines the role of entrepreneurial leadership in fostering innovation and achieving start-up success. By analyzing leadership styles, decision-making processes, and team dynamics, the research identifies key factors that contribute to sustained growth and competitiveness. Findings suggest that visionary leadership combined with adaptive strategies is essential for navigating challenges in dynamic markets.